MULTI-DIMENSIONAL SUSTAINABILITY ASSESSMENT IN MICRO-BUSINESS OF SIAMESE FIGHTING FISH CULTIVATION DURING THE COVID-19 PANDEMIC - Sukwika, Tatan; Sukamdani, Nugroho B (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
The economic value of Siamese Fighting fish and betta fish (Betta splendens) cultivation at the micro-business level has good potential to be developed during the COVID-19 pandemic. Considering the potential of the betta ornamental fish business, not a few parties use this as an alternative solution to the community's income crisis. During the COVID-19 pandemic, many parties engaged as ornamental fish cultivators to become a commodity of economic value, which in the past was usually only fish for complaints and not specifically cultivated to become aesthetic fish. The research objective focuses on assessing multi-dimensional sustainability in micro-business Betta splendens aquaculture during the pandemic. The data collected in this study include primary data and secondary data. Primary data was collected based on a questionnaire through interviews with micro-business actors of betta fish spread across six villages community associations, while secondary data was collected based on reports, journals, and the results of relevant studies. Data analysis used multi-dimensional scaling (MDS), leverage test, and Monte Carlo test. The analysis results show that two dimensions are categorized as less sustainable, namely business feasibility and business strategy, and three other dimensions, namely market networks, infrastructure, and maintenance and handling categorized as moderately sustainable. Ten sensitive attributes are considered unstable. The conclusion of the five dimensions assessed shows a less sustainable category. Leveraging factors in each dimension can be a key to developing a sustainable strategy for micro-business siamese fighting fish farming in the future.